Detection of hybrids in nature: application to oaks (Quercus suber and Q. ilex). (Heredity, 2009)
Powerful and accurate detection of first-generation (F1) hybrids and backcrosses in nature is needed to achieve a better understanding of the function and dynamics of introgression. To document the frequency of ongoing interspecific gene exchange between two Mediterranean evergreen oaks, the cork oak (Quercus suber) and the holm oak (Q. ilex), we analyzed 1487 individuals originating from across the range of the two species using eight microsatellite loci and two Bayesian clustering approaches (implemented in the programs STRUCTURE and NEWHYBRIDS). Simulated data were used to assess the differences between the two clustering methods and to back up the choice of the threshold value for the posterior probability to discriminate admixed from pure individuals. We found that the use of STRUCTURE resulted in the highest power to detect hybrids, whereas NEWHYBRIDS provided the highest accuracy. Irrespective of the approach, the two species were clearly distinguished as independent genetic entities without any prior information. In contrast with previous reports, we found no evidence for unidirectional introgression. The overall hybridization rate was very low (<2% of introgressed individuals). Only two individuals were identified as F1 hybrids and five as early backcrosses. This work shows that the combined application of the two complementary Bayesian approaches and their systematic validation with simulations, fit for the case at hand, helps gain resolution in the identification of admixed individuals.

Allozyme variation in cork oak ( Quercus suber L.): the role of phylogeography and genetic introgression by other Mediterranean oak species and human activities (TAG Theoretical and Applied Genetics, 1998)
Genetic variation in the cork oak (Quercus suber L.) was investigated using 11 loci from seven enzyme systems in 40 populations sampled over the entire distribution of this species in the western Medi- terranean Basin. Mean heterozygosity values over the polymorphic loci (Ho"0.283), the percentage of poly- morphic populations (M"0.76), and the total genetic diversity (Ht"0.31) from which 11% was accounted for among-population variation, are among the highest recorded in oak species. In contrast to previous results in holm oak (Q. ilex L.), another evergreen species in the same area, cork oak possessed a smaller allele pool and a lower average number of alleles per locus and per population (A"2.0). More particularly, very few low- frequency alleles were observed in cork oak except for eight populations in which allozyme polymorphism at locus Pgi 1, diagnostic between both species, indicates that these low-frequency alleles are introgressed from holm oak. On the basis of the genetic distance esti- mated from allozyme frequencies, 32 of the 40 cork oak populations studied were classiÞed into two very distinct sets which also corresponded to distinct geographic areas. One set gathered together the 18 populations from the Iberian peninsula and two adjac- ent areas in France, i.e. the centre of origin of cork oak, according to paleobotanical data. This set was charac- terized by a larger allele pool, a higher within-popula- tion genetic diversity and a lower di¤erentiation between populations than was observed in the other set, which comprised the populations from North Africa, Sicily, Sardinia, Corsica, continental Italy and the region of Provence (southeastern France). In these Communicated by P. M. A. Tigerstedt L. Toumi1 á R. Lumaret ( ) Centre dÕEcologie Fonctionnelle et Evolutive (C.E.F.E., C.N.R.S.), F-34293, Montpellier Cedex 05, France Present address: 1 Institut Sylvo-Pastoral, 8110 Tabarka, Tunisia more southern and eastern disjunct areas, cork oak migration from Iberia may have occurred at di¤erent periods since the end of the Tertiary. The possible e¤ect of human activity on cork oak genetic structure, i.e. the selection of good-quality cork, acorn over-use for ani- mal food, and even human nutrition, is discussed.

Effect of geographical discontinuity on genetic variation in Quercus ilex L.(holm oak). Evidence from enzyme polymorphism (Heredity, 1995)
Allozymes at a maximum of eight loci were used to analyse the spatial patterns of genetic variation in 1942 hoim oak trees (Quercus ilex L.) from 57 provenances distributed in the six main disjunct areas of the species distribution area. Polymorphism and genetic diversity were high except in the six marginal populations growing in various locations under unfavourable climatic conditions. Ten per cent of the total genetic diversity (H =0.262) was accounted for by among-population variation. In this long-lived species, the effect of geographical discontinuities on gene flow restriction was shown by the occurrence of: (i) numerous rare alleles limited to a single disjunct region; and (ii) allele frequency variation among the disjunct regions for four alleles. This result was obtained by comparing spatial autocorrelograms from the 57 populations of the entire distribution area and from the 31 populations of the Mediterranean continental region which constitutes the largest continuous area in that distribution. Life history traits (e.g. long life span and high outcrossing rate) and past changes in climate and geographical continuity are assumed to be the main factors responsible for the present genetic variation patterns observed in the species.

Distribution spatiale des génotypes dans une population de chêne vert (Quercus ilex L.), flux génique et régime de reproduction (Genetics Selection Evolution, 1988)
Spatial distribution of genotypes in holm oak (Quercus ilex L.) was analyzed within a site using three allozyme systems (PGI-I, IDH-1, ADH-1) as markers. No aggregation effect of the genotypic classes could be pointed out at any locus. Wright’s fixation index calculated over all the individuals of the site was not significantly different from zero (Fis = 0.02), indicating a situation close to the Hardy-Weinberg equilibrium expectation. Allele frequencies in the effective pollen responsible for the observed progenies of nine open-pollinated individual trees of the site were significantly different (P < 0.05) even when the parents were very close. Finally, the results clearly show that the trees are not necessarily pollinated by their neighbours, but rather by those individuals that are both synchronous phenologically and that invest primarily in the male function.